The Impact of Healthcare Service Quality and Patient Experience on Patient Loyalty and Patient Trust as Mediation (Survey on Outpatient Patients at Muhammadiyah Hospital Bandung) - Zulfa Zakiah Rachmatillah; Fansuri Munawar (Dinasti Publisher, 2025)
This study aims to analyze the influence of service quality and patient experience on patient loyalty, with trust as a mediating variable at Muhammadiyah Hospital in Bandung City. The method used is descriptive and verification analysis with the Structural Equation Modeling - Partial Least Squares (SEM-PLS) approach. The results show that service quality and patient experience have a positive and significant impact on patient loyalty. Moreover, patient trust is proven to be a mediating variable that strengthens the relationship between service quality and patient experience with loyalty. This means that the better the service quality and patient experience provided by the hospital, the higher the patient trust, ultimately leading to greater patient loyalty. These findings provide implications for hospital management to focus more on improving service standards and patient experience to build stronger trust and loyalty.